Direction of Lateral Traction in Ejnell's Technique: An Experimental Study and Case Report of Bilateral Vocal Cord Paralysis - Tamura, Etsuyo; Kitahara, Satoshi; Ogura, Masami; Hiroi, Sadayuki (Acta Oto-Laryngologica, 2002)
In order to develop the method of laterofixation of the vocal cord (Ejnell's method) in cases of bilateral vocal cord paralysis, six autopsy specimens of normal larynx were obtained. We inserted traction sutures under conditions of direct visualization and studied the relationship between the direction of the traction exerted by the suture and subsequent enlargement of the glottis. When the vocal cord was pulled perpendicular to the thyroid cartilage wing, the mean glottal area was 106.2% of its area before traction. When the vocal cord was pulled perpendicular to the median line of the glottis, the mean glottal area was 112.7% of its area before traction. The latter angle of traction therefore produced more efficient enlargement of the glottis ( p < 0.05; paired t -test). Based on an anatomic study of cadaveric laryngeal regions, a formula was developed to predict at which point the needle should be placed in order to produce optimal results using Ejnell's technique. Further clinical studies will be carried out in patients to test the validity of this formula.